Low back pain among nurses as related to work environment: A cross-sectional observational study - Ngozi Rosemary Osunde; Chinomso Ugochukwu Nwozichi; Olaolorunpo Olorunfemi; Jaminat Omotade Sodimu; Omotayo Mercy Olorunfemi (Current Medical Issues, 2023)
Background: Low back pain (LBP) is a major problem in the nursing profession and it is been reported that more nurses experience LBP during the nursing practice. Studies show that only 15.9% of nurses had LBP before coming into nursing while 84.5% complained they had LBP after working in the nursing environment. Aim: The aim of this study was to determine factors responsible for low back ache, as related to the work environment in the University of Benin Teaching Hospital, Benin City, Nigeria. Materials and Methods: A cross-sectional descriptive study was conducted from January 2019 to February 2020, with probability sampling to select a sample size (n = 260). Data collected were analyzed using tables; percentages, bivariate analysis, and and multivariate logistic regression were used for data analysis at 0.05 level of significance, through a statistical package for the social science software. Results: Among 260 nurses with backache, 159 (61.15%) were male and most of the participants' ages were between 25 and 34 years, with a mean age of 26.5 (0.37). The multivariate logistic regression analysis showed that heavy manual lifting (odd ratio [OR] 0.21, 95% confident interval [CI] 0.54–0.73), body posture (OR 0.31, 95% CI 0.20–1.08), the length of working shift (OR 0.60, 95% CI 0.74–0.86), awkward postures (OR 0.68, 95% CI 0.65–1.10), and prolonged standing during nursing care (OR 0.73, 95% CI 0.52–1.00) were the major factors for LBP among nurses, with <0.001, 0.001, 0.002, 0.002, and 0.003, respectively. Conclusions: The finding implies that all effort should be directed toward policies which have positive effects on proper management of the work environment and other conditions, such as health and safety training. Prevention of work overloads through appropriate work shifting, and the mechanism of body posture should be improved. Furthermore, periodical flexing of feet, knees, and hip is necessary in a condition where there is a need to stand for a long period of time.